Can Product Quality Improve Purchase Decisions in E-Commerce and Social Media through Customer Loyalty and Trust? - Nofrizal, Nofrizal; Sucherly, Sucherly; Juju, Undang; Khairani, Zulia; Soviyanti, Efrita; Hadiyati, Hadiyati; N, Arizal (Binus Business Review, 2023)
The in online sales transactions have continued to increase due to several factors, such as the improvement of Internet quality, the growth of start-ups in Indonesia, and the COVID-19 pandemic’s effects, which have restricted customers from making purchases offline. The research aimed to identify different types of direct and indirect influences that caused customers to make purchase decisions for fashion products and determine more dominant group (women or men) on e-commerce platforms and social media. The research applied a quantitative method. The research respondents were 244 customers who bought fashion products in e-commerce and social media. The analytical tools were Structural Equation Modelling (SEM) with SmartPLS 4.0, convergence and discrimination invalidity for the validity test, composite reliability for the reliability test, and structural model evaluation (inner model). The findings indicate that all aspects of product quality, trust, and customer loyalty have a huge impact on buying fashion products in e-commerce and social media. Moreover, in the indirect effect, product quality affects customer loyalty through trust. Similarly, product quality impacts purchase choices through customer loyalty. Trust also affects purchase choices through customer loyalty. Then, product quality affects purchase decisions through trust. Last, product quality has an impact on purchase decisions through customer loyalty and trust. Additionally, the results of PLS-MGA show that women are more dominant in buying fashion products on e-commerce and social media than men.